The Effect of Brand Trust on Brand Loyalty of Dodol Bestory Study of PD. Bestari Diamond Garut - Taopik Hidayat; Suca Rusdian; Ima Apriliani (PT Inovasi Pratama Internasional, 2022)
This research is motivated by the loyalty of the dodol bestory arrowroot brand loyalty to PD. Intan Bestari Garut who is experiencing sales instability. This is caused by several factors, one of which is brand trust. The purpose of this study was to find out how the effect of brand trust on brand loyalty on dodol bestory products in PD. Diamond Bestari Garut. Based on the results of data processing obtained using SPSS version 24, the instrument has been tested for validity and reliability and the results are valid because each item produces an r value of more than 0.30 and a reliability of 0.753 for brand trust and 0.744 for brand trust. Brand Loyalty. And it is known that the effect of brand trust on brand loyalty is 0.678, which means there is a unidirectional (positive) relationship which is included in the strong category, with a contribution of 35.2% to brand loyalty while 64.8% is influenced by other factors. not discussed in this study. . And the last is hypothesis testing using the t test where it is known that the t value is 6.027, which means 6.027 > t table 1.996 and the sig value is 0.000 <0.005, so it can be concluded that the hypothesis in this study Ho is rejected and Ha is accepted, which means Brand Trust (X ) positive and significant effect on Brand Loyalty (Y) on PD. Diamond Bestari Garut. So, the hypothesis proposed can be accepted.